Species diversity of Odonata in the urban ecosystem of Iligan City, Philippines - DRANREB P. BANAYBANAY; OLIVE A. AMPARADO; LADY JANE G. MORILLA; LEONARDO A. ESTAÑO (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Banaybanay DP, Amparado OA, Morilla LJG, Estaño LA. 2024. Species diversity of Odonata in the urban ecosystem of Iligan City, Philippines. Biodiversitas 25: 890-899. Urbanization impacts ecosystem function and services, resulting in changes in ecological processes, increasing human population, and biodiversity loss. This threat may influence Odonata species' abundance, diversity, and distribution in freshwater habitats. The survey of Odonata in the urban ecosystem in Iligan City was carried out from December 2022 to March 2023 to determine the species diversity, abundance, endemism, distribution, and their correlation to various environmental parameters in freshwater habitat in this area. Field sampling was conducted in six identified barangays: Barangay Tubod, Bagong Silang, Del Carmen, Villa Verde, Poblacion, and Ubaldo Laya. The study recorded 569 individuals consisting of two major Odonate families, the Family Libellulidae, comprising nine species: Acisoma panorpoides, Brachydiplax chalybea, Crocothemis servilia, Diplacodes trivialis, Neurothemis terminata, Neurothemis ramburii, Orthetrum sabina, Rhodothemis rufa and Trithemis aurora; and Family Coenagrionidae with four species: Agriocnemis femina, Ceriagrion lieftincki, Ischnura senegalensis and Pseudagrion pilidorsum. Among the recorded species, I. senegalensis (34.80%) was found to be the most abundant species, followed by A. femina (32.51%) and O. sabina (10.54%), which are encountered in all sampling sites. Meanwhile, the low diversity and low endemism (7.69%) were recorded in all sampling areas, with C. lieftincki as the only Philippine endemic recorded in Iligan City Wet Park and Barangay Bagong Silang. Canonical correspondence analysis reveals that environmental factors such as air temperature, water temperature, water pH, water turbidity, and relative humidity are crucial parameters in determining the assemblage of Odonata. Overall, urban ecosystems in Iligan City are dominated by oriental species, signifying that the areas are heavily disturbed. Therefore, urgent management of urban ecosystems is required to enhance the city's ecological health, sustainability, and insect biodiversity.